2018
DOI: 10.1155/2018/7027624
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship between Atherogenic Index of Plasma and Cardiovascular Disease Risk Factors among Staff of an University in Malaysia

Abstract: Background Atherogenic index of plasma (AIP) was found to be one of the strongest markers in predicting the cardiovascular disease (CVD) risk. This study was to determine the AIP and its relationship with other CVD risk factors. Materials and Methods This cross-sectional study was done among 349 staff of a public university in Sarawak. Data were collected using questionnaire, blood sampling, and anthropometric and blood pressure measurement. Data were analyzed using IBM SPSS version 20. Results A total of 349 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
65
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 22 publications
9
65
1
6
Order By: Relevance
“…These findings were similar to previous studies [39,40]. Besides, likewise former findings all lipid profile and AIP showed a significantly positive correlation, while a significant negative correlation was found between HDL and AIP in both groups [41,42]. Dietary fatty acids, determine the risk and protection of chronic diseases due to the chain length, number, and position of the double bonds as well as their shape (cis or trans) [43][44][45].…”
Section: Discussionsupporting
confidence: 91%
“…These findings were similar to previous studies [39,40]. Besides, likewise former findings all lipid profile and AIP showed a significantly positive correlation, while a significant negative correlation was found between HDL and AIP in both groups [41,42]. Dietary fatty acids, determine the risk and protection of chronic diseases due to the chain length, number, and position of the double bonds as well as their shape (cis or trans) [43][44][45].…”
Section: Discussionsupporting
confidence: 91%
“…These findings were similar to previous studies [41,42]. Besides, likewise former findings all lipid profile and AIP showed a significantly positive correlation, while a significant negative correlation was found between HDL and AIP in both groups [43,44]. Dietary fatty acids, determine the risk and protection of chronic diseases due to the chain length, number, and position of the double bonds as well as their shape (cis or trans) [45][46][47].…”
Section: Discussionsupporting
confidence: 91%
“…Several cross-sectional studies have shown that chronic diseases such as hypertension, dyslipidemia, and CVD are more prevalent in obese individuals [60]. According to the findings of the previous studies, there is a direct relationship between an increase in the blood atherogenic index and obesity, which ultimately predicts CVD [44]. Therefore, taking care of healthy food intake is an important factor to prevent chronic disease for all people.…”
Section: Discussionmentioning
confidence: 98%
“…(AIP) was calculated as logarithmic transformation of the ratio of TG to HDL‐C. log 10 (TG/HDL‐C; Bo et al, )…”
Section: Methodsmentioning
confidence: 99%
“…(AIP) was calculated as logarithmic transformation of the ratio of TG to HDL-C. log 10 (TG/HDL-C; Bo et al, 2018) If Tg > 400 mg/dl, Low density lipoprotein was calculated according friedewald formula.…”
Section: Biochemical Measurementmentioning
confidence: 99%